Tension-filled Governance?: Exploring the Emergence, Consolidation and Reconfiguration of Legitimatory and Fiscal State-crafting - Tim Holst Celik (Copenhagen Business School (CBS), 2017)
Since the crisis-engrossed 1970s, and especially the 1990s, `governance' has become a dominant concern and concept; notably, within particularly political science, a certain diagnosis explicitly or implicitly focused on a shift `from government to governance' has become increasingly popular. This study examines the governance phenomenon of the post-1970/1990s period from a state-situated and historically informed perspective. Specifically, taking initial analytical departure in an approach of the early 1970s associated with James O'Connor, Jürgen Habermas and Claus Offe focused on the statesituated tension-filled functional relationship between legitimation and accumulation, the study both historically and theoretically reworks this approach and reapplies it for the post-1970s/1990s governance period. It asks whether and to what extent governance has served as a distinctive post- 1970s/1990s state-facilitated way of bridging/altering the tension-filled relationship between legitimation and fiscal accumulation in Western European liberal-capitalist democratic polities.
hdl:10398/9481
Keywords: 650